2009
DOI: 10.1007/s12594-009-0092-y
|View full text |Cite
|
Sign up to set email alerts
|

Light hydrocarbons geochemistry of surface sediment from petroliferous region of the Mehsana block, North Cambay Basin

Abstract: A study was carried out to test the usefulness of surface geochemical methods as regional evaluation tools in petroliferous region of the Mehsana block, North Cambay Basin. A suite of 135 soil samples collected from the depth of 2.5 m, were analyzed for adsorbed light gaseous hydrocarbons and carbon isotopes (@ 13 C methane and @ 13 C ethane ). The light gaseous hydrocarbon analysis show that the concentration ranges 402 ppb, 135 ppb, 70 ppb, 9 ppb and 18 ppb of C 1 , C 2 , C 3 , iC 4 and nC 4 , respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…A recent study reported by Madhavi et al (2009) to assess the efficacy of surface geochemical methods as exploration tool in petroliferous region of the Mehsana block, North Cambay Basin have shown good correlation of surface geochemical anomalies with the major generative depressions of oil and/or gas field of Sobhasan/Linch areas. Therefore, adsorbed soil gas surveys are considered to be rapid and cost effective for initial evaluation of frontier basins.…”
mentioning
confidence: 99%
“…A recent study reported by Madhavi et al (2009) to assess the efficacy of surface geochemical methods as exploration tool in petroliferous region of the Mehsana block, North Cambay Basin have shown good correlation of surface geochemical anomalies with the major generative depressions of oil and/or gas field of Sobhasan/Linch areas. Therefore, adsorbed soil gas surveys are considered to be rapid and cost effective for initial evaluation of frontier basins.…”
mentioning
confidence: 99%
“…The C 1 , C 2 , C 3 , nC 4 , iC 4 and C 2+ show linear relationship among themselves, suggesting that all the hydrocarbon constituents in microseep are genetically related and least influenced by secondary alterations during migration of microseeps from the sub surface to the surface and their subsequent adsorption on the soils. The carbon isotopic data of methane and ethane indicates thermogenic source for the adsorbed soil gases (Madhavi et al, 2009). The thermogenic origin of these hydrocarbons is further confirmed by absence of correlation between ΣC 2+ and TOC (Total organic carbon) and TIC (Total inorganic carbon) content in the soil samples.…”
Section: Discussionmentioning
confidence: 71%
“…The 0.5 ml of the gas was injected in to the Varian CP-3380 Gas chromatograph equipped with Flame ionization detector for quantification of light hydrocarbons. Carbon isotopic composition of light hydrocarbons (δ 13 C 1 and δ 13 C 2 ) in soil samples is determined using GC-C-IRMS, which comprises of Agilent 6890 GC coupled to a Finnigan-Delta Plus XP Isotope Ratio Mass Spectrometer via a GC combustion III interface (Madhavi et al, 2009). The TOC and TIC were measured by Elementar Liqui TOC analyzer with the solid sample module.…”
Section: Sampling and Laboratory Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on organic geochemical exploration concern the analysis of light gaseous hydrocarbons in recent sediments because these compounds migrate easier than the heavier, liquid hydrocarbons 7 . Hydrocarbons reaching the surface can be measured directly both in the sediments and in the overlying air or water 2,[7][8][9][10][11][12] . The anomalous concentrations of hydrocarbon gases like methane, ethane and propane in surface soils serve as direct evidence for the presence of a petroleum system in and around the area 2,13 .…”
mentioning
confidence: 99%